A STUDY OF ISLAMIC LEGAL PHILOSOPHY OF THE CONCEPT OF COLLECTIVE PROPERTY IN INDONESIA BASED ON CORRECTIVE JUSTICE AND THE ISLAMIC EDUCATION MODEL - Harahap, Rifnatul Hasanah; Pagar, Pagar; Syam, Syafruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Analysis of the Concept of Joint Assets in the Compilation of Islamic Law reviewed Based on Corrective Justice Values is an Islamic law study that discusses legal issues regarding joint assets. Based on the reality and legal developments that occur in Indonesian society, which is very dynamic, and from several court decisions, it was found that, in general, the panel of judges at the Religious Courts, in deciding cases for claims for the distribution of joint assets, did not depart from these laws and regulations, namely by dividing joint property equally (half share) between husband and wife. This rule causes many problems that occur when practicing the rulings of the religious courts, because not a few people consider that the distribution of joint assets does not fulfill a sense of justice. For this reason, it is necessary to understand in detail the distribution of joint assets based on the inculcation of Islamic values through education. This research model (mode of inquiry) is qualitative. While the approach used is philosophical legal research, In conclusion, this study shows that the distribution of joint assets between ex-husband and ex-wife, based on the value of corrective justice, should be divided according to the amount of effort between the two in obtaining assets during marriage, dividing equally (50:50, Article 97 KHI). is considered that there are times when not fulfilling a sense of justice is necessary when one party has committed an act that is detrimental to the other party (husband or wife) because it does not carry out what has become its obligation in the long term.